Assembly and phylogenetic analysis of the complete chloroplast genome sequence of Gentiana scabra Bunge. Issue 2 (2nd April 2020) - Shang, Mingyue; Meng, Xiangxiao; Yan, Fulin; Qian, Jun; Duan, Baozhong; Wang, Ying
Abstract: The first complete chloroplast (cp) genome of Gentiana scabra was determined from Illumina paired-end sequencing data in this study. The cp genome of G. scabra is 146, 915 bp in length with 37.84% overall GC content, including a large single copy (LSC) region of 79, 350 bp and a small single copy (SSC) region of 17, 027 bp, which are separated by a pair of inverted repeats (IRs) of 25, 269 bp. The cp genome is composed of 130 genes, including 85 protein-coding genes, 8 rRNA genes, and 37 tRNA genes. Phylogenetic analysis indicated that the G. scabra is more closely related to subfamily of Gentianoideae than Menyanthaceae.